Convergence of algorithms for fixed points of generalized asymptotically quasi-ϕ-nonexpansive mappings with applications - Qin, Xiaolong; Agarwal, Ravi P; Cho, Sun Young; Kang, Shin Min (Fixed point theory and applications (Hindawi Publishing Corporation), 2012)
In this article, strong convergence of Krasnoselski-Mann iterative sequences and Halpern iterative sequences are investigated based on hybrid projection methods. Strong convergence theorems for common fixed points of a family of generalized asymptotically quasi- ϕ -nonexpansive mappings are established in the framework of Banach spaces. Mathematics Subject Classification 2000 : 47H09; 47J05; 47J25